Implementasi Bcrypt dengan SHA-256 pada Password Pengguna Aplikasi Golek Kost - Rynaldy Shulton Giffary; Erika Ramadhani (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Brute force is the breaking of passwords in the SHA¬-256 algorithm, so that systems using this algorithm are easy to retrieve important data. In addition there is MD5 which can cause collusion. However, there is an algorithm that can withstand brute force attacks, namely bcrypt. Personal data security is a top priority on every system. Brute force is a cyber crime that needs to be watched out for. The purpose of this study is to examine the bcrypt algorithm used as a password in order to be able to survive brute force attacks. Because bcrypt has a cost and a salt value